Quatre postures de valorisation et d’évaluation des paysages dans les régions de montagne : le designer, le planificateur, le gestionnaire et le scientifique - Pierre Donadieu; Gaelle Aggeri (Projets de Paysage, 2011)
The authors analyze a sample of achievements of landscape strategies and management practices of public spaces, selected in Europe (particularly in highland regions). They show how landscape professionals “landscape designers, planners, managers, scientists” find alternative solutions to understand and propose ways to keep together the forms, functions and social uses of spaces that they create or they seek to control the future. These four professional positions translate into practice the four sides of territorial projects relayed by their political and social actors.